Development of Rammed Earth Material Technology by Utilizing Plastic Waste as Reinforcement on The Partition Walls of The Building Room - Kinanti Wijaya; Sutrisno Sutrisno; Harun Sitompul; Nono Sebayang; Ruri Aditya Sari; Iswandi Idris (Journal of Applied Engineering and Technological Science (JAETS), 2025)
In order to improve the compressive and bending strength of rammed earth materials for use in partition walls, this study investigates the incorporation of plastic trash. The goal of the research is to enhance the performance of sustainable construction materials while addressing the environmental problem of plastic waste. Using a Universal Testing Machine (UTM), compressive and bending strength tests were performed after 30 days for rammed earth mixtures containing four different amounts of plastic trash (0%, 1%, 3%, and 5%). According to the findings, adding plastic trash can increase compressive strength by up to 3%, reaching a maximum strength of 5.17 MPa. However, compressive and bending strength significantly decreased when the plastic percentage was increased over 3%, with the 5% plastic showing the worst performance. According to these results, plastic trash can enhance material performance, but its use requires careful optimization. By putting forth a novel technique for recycling plastic trash, the study supports sustainable building practices and provides a workable substitute for non-load-bearing applications such as partition walls. This study advances our understanding of green building technologies and offers workable ways to cut down on plastic waste in the building industry.